PENERAPAN MODEL PEMBELAJARAN GAMIFIKASI DALAM MENINGKATKAN HASIL BELAJAR DI MTS AL-MUNAWWARAH LUMU KABUPATEN MAMUJU TENGAH - Rosdina; Mustamin; Wahab, Abdul; Akil, M; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement of student learning outcomes through the application of the Gamification learning model in the subject of Akidah Akhlak class VIII.A at MTs Al-Munawwarah Lumu, Central Mamuju Regency. This study is motivated by the low learning outcomes of students caused by the use of learning methods that are still dominated by lecture methods so that students are less active and less motivated in participating in learning. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model which consists of the planning stage, action implementation, observation, and reflection carried out in two cycles. The research subjects were 32 students of class VIII.A. Data collection techniques were carried out through observation, interviews, documentation, and tests, while the data were analyzed using qualitative and quantitative descriptive analysis. The research results show that the application of the Gamification learning model is able to improve student learning outcomes. At the pre-cycle stage, only 3 students (9.37%) achieved the Minimum Completeness Criteria (KKM) with an average score of 39.37. After the actions in Cycle I, the number of students who completed increased to 20 people (62.5%). Furthermore, in Cycle II learning completion increased to 30 students (93.75%), so that they had met the specified success indicators. Teacher activity also increased from 75% in the good category in Cycle I to 87.5% in the very good category in Cycle II, while student activity increased from 78.12% to 90.62% in the very good category.